Technological Approach To The Educational Process In Primary Schools - A Factor To Increase Educational Efficiency - Ilmira Setsaliyeva Ismoilovna; Gulmira Mukhamatova (Universitas Muhammadiyah Sidoarjo, 2022)
Educational technologies cover a specific area of pedagogical activity. Constructing the stages of the didactic process in a certain sequence means the organization of students' learning activities using selected teaching methods in accordance with the objectives set for the topic. Teaching methods, by their nature and content, belong to one or another classification based on a certain pedagogical theory. When considering their effectiveness, it is important to ensure that all educational institutions achieve the goal of teacher-student interaction, which can regulate and direct the teaching process.